2014
DOI: 10.1186/1471-2407-14-469
|View full text |Cite
|
Sign up to set email alerts
|

Association between the TP53 codon 72 polymorphism and risk of oral squamous cell carcinoma in Asians: a meta-analysis

Abstract: BackgroundSeveral epidemiological studies have previously investigated the association between the TP53 codon 72 polymorphism and oral squamous cell carcinoma (OSCC) susceptibility; however, current results are inconsistent. We therefore performed this meta-analysis to thoroughly investigate any association among Asian patients.MethodsA comprehensive search of PubMed and Embase databases was performed up to December 2013. We only considered studies consisting of patients diagnosed with OSCC by pathological met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…A common single nucleotide polymorphism (SNP) of p53 at codon 72 in exon 4 results in a substitution of Pro for Arg in the transactivation domain [26]. The common Arg variant allele may alter the susceptibility of p53 to oncogenic HPV E6-mediated degradation [27], and this allele has been associated with oncogenic HPV infection [28,29,30 ]. Furthermore, in case-control analyses, the homozygous Arg/Arg genotype has been significantly associated with an increased risk of HPV-associated cancer [27,31].…”
Section: Cell Cycle Control Polymorphisms and Hpv Infectionmentioning
confidence: 99%
“…A common single nucleotide polymorphism (SNP) of p53 at codon 72 in exon 4 results in a substitution of Pro for Arg in the transactivation domain [26]. The common Arg variant allele may alter the susceptibility of p53 to oncogenic HPV E6-mediated degradation [27], and this allele has been associated with oncogenic HPV infection [28,29,30 ]. Furthermore, in case-control analyses, the homozygous Arg/Arg genotype has been significantly associated with an increased risk of HPV-associated cancer [27,31].…”
Section: Cell Cycle Control Polymorphisms and Hpv Infectionmentioning
confidence: 99%
“…A meta-analysis by Zeng et al [25] reported that the TP53 polymorphism is not associated with HPV-negative oral squamous cell carcinoma in Asians, and they also reported that a subgroup analysis demonstrated an association between TP53 polymorphisms and HPV-associated oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor protein p53 (TP53) is a frequently mutated gene in human cancers, once mutated gains oncogenic role [2][3][4]. Metaphorically speaking, when the guardian of the genome TP53 fails, it leads to the activation of the early carcinogenic events [5].…”
Section: Introductionmentioning
confidence: 99%